2022
DOI: 10.1007/s00394-022-02956-2
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of young child formulae in the Netherlands

Abstract: Purpose Adequate micronutrient intakes are essential for young children. Special young child formulae (YCF) intended for children from 1 year old are available in the Dutch market. Since YCF are enriched with many micronutrients, it has the potential to have a beneficial effect on young children, or might pose a risk on excessive micronutrient intakes. The current study investigated the characteristics of YCF users, and the effect of YCF use on micronutrient intakes. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…For the fish purees, iron had the highest concentration for name brands and zinc for store brands (Table 1). This finding was consistent with other nutritional analyses that reported higher iron and zinc intakes among children who consumed this kind of formulae [35,36]. We observed significant differences in molybdenum, chromium, zinc, and selenium concentrations between the different types of brands.…”
Section: Content Of Chemical Elements In Ready-to-eat Purees For Babiessupporting
confidence: 92%
See 1 more Smart Citation
“…For the fish purees, iron had the highest concentration for name brands and zinc for store brands (Table 1). This finding was consistent with other nutritional analyses that reported higher iron and zinc intakes among children who consumed this kind of formulae [35,36]. We observed significant differences in molybdenum, chromium, zinc, and selenium concentrations between the different types of brands.…”
Section: Content Of Chemical Elements In Ready-to-eat Purees For Babiessupporting
confidence: 92%
“…The presence of REEs and other MEs in food has been observed before [ 26 ], so children’s food should not be an exception. In general, REE concentrations in food are quite variable and low but have been reported in a wide range of foods, including fresh vegetables, rice, cereals, fresh aquatic products, fresh meats, and eggs [ 35 , 41 ]. To our knowledge, this is the first time that many of these chemical elements have been analyzed in ready-to-eat purees for babies.…”
Section: Resultsmentioning
confidence: 99%
“…The data on individual food intakes showed that the use of follow-on toddler formulas contributes to intakes from fortified foods for this age group (results not shown). Approximately 20% of toddlers in this survey use follow-on infant formula: Formula users had higher intakes of vitamins B1, B2, folic acid, C, D, E, and iron and zinc, and an increase in the proportion exceeding the UL for zinc [ 38 ]. In a Spanish population, the use of fortified milk including follow-on formula improved adequacy in zinc, vitamin A and vitamin E, while the proportion of children exceeding the UL also increased for zinc and vitamin A for the youngest age group.…”
Section: Discussionmentioning
confidence: 99%
“…According to a number of studies, including randomized clinical trials [14][15][16], YCF has been shown to improve young children's nutritional intakes as well as the overall diet quality as indicated by a higher probability of nutrient adequacy [17][18][19][20][21]. The consumption of YCF seems to be a particularly successful approach to meet the nutritional requirements for children at risk of nutrient deficiencies, such as vitamin D, iron, vitamin A, calcium, and LCPUFAs, which are key nutrients for healthy growth and development [14,16,18,22]. To date, limited available evidence exists for the potential impact of YCF on growth outcomes.…”
Section: Introductionmentioning
confidence: 99%